2013
DOI: 10.1051/0004-6361/201321201
|View full text |Cite
|
Sign up to set email alerts
|

Jupiter’s zonal winds and their variability studied with small-size telescopes

Abstract: Context. The general circulation of Jupiter's atmosphere at cloud level is dominated by a system of zonal jets that alternate in direction with latitude. The winds, measured in high-resolution images obtained by different space missions and the Hubble Space Telescope, are overall stable in their latitude location with small changes in intensity at particular jets. However, the atmosphere experiences repetitive changes in the albedo of particular belts and zones that are subject to large-scale intense disturban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Tentatively, one can identify these features as delineating a southern jet peak, symmetric in latitude to the northern one. If so, Saturn's Equatorial jet at the lowest levels sampled has a similar shape to the Jupiter equatorial jet, that is, exhibiting a ‘double symmetric peak' relative to Equator13456. Third, the red continuum 689–750–937 nm wavelengths show a second group of lower velocities that follow the 2014 profile from Cassini ISS (blue and violet lines, Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Tentatively, one can identify these features as delineating a southern jet peak, symmetric in latitude to the northern one. If so, Saturn's Equatorial jet at the lowest levels sampled has a similar shape to the Jupiter equatorial jet, that is, exhibiting a ‘double symmetric peak' relative to Equator13456. Third, the red continuum 689–750–937 nm wavelengths show a second group of lower velocities that follow the 2014 profile from Cassini ISS (blue and violet lines, Fig.…”
Section: Resultsmentioning
confidence: 91%
“…At the upper cloud level, the giant planets Jupiter and Saturn display a permanent system of alternating eastward and westward zonal jets whose intensity and width show few temporal changes since the first detailed measurements in 1979–1980 (refs 1, 2, 3, 4, 5, 6, 7, 8, 9). One exception is Saturn's broad equatorial jet that extends from planetographic latitudes ∼35° N to 35° S reaching eastward peak velocities ∼450–500 ms −1 (refs 7, 8, 9) (Fig.…”
mentioning
confidence: 99%
“…The motivations to obtain the ground‐based zonal winds were the following: Explore the possibility of small temporal changes in the zonal winds at different latitudes over 2016. A full statistical analysis of the ground‐based data from December 2015 to June 2016 and a comparison with HST zonal winds measured in January 2015 [ Simon et al , ] including a specific exploration of the NTB jet (not shown) conclude that there were no changes in the zonal winds at any latitude below the amateur noise level (10 m s −1 for the worse statistics associated to data from individual months). Validate the technique for ground‐based data which provides results that largely improve in terms of better latitudinal resolution and smaller error bars over previous analyses with similar data [ Barrado‐Izagirre et al , ]. …”
Section: Zonal Windsmentioning
confidence: 99%
“…The quality and spatial resolution on these images depend on several parameters: planet size (date of the observations relative to Jupiter's opposition), atmospheric conditions (seeing), telescope diameter, camera used and processing software, planet altitude, and astronomer's location in latitude. Assuming 35 cm diameter as a representative size of telescope used, the Airy spot diameter at the yellow wavelength is 0.4 arcsec, which for a JupiterEarth distance (∼6.26 × 10 8 km) gives a spatial resolution over Jupiter's disk of ∼1200 km/pixel; this is good enough to study Jovian atmospheric dynamics (Barrado-Izagirre et al 2013).…”
Section: Observationsmentioning
confidence: 99%